"In der Zwickmühle der Zeit": Marieluise Fleißer's Mehlreisende Frieda Geier (1931) and the Non‐Simultaneities of Gendered Subjectivity. (23rd November 2020) - DeSocio, Domenic
Abstract : Adapting Ernst Bloch's concept of "Ungleichzeitigkeiten, " this paper interrogates how non‐simultaneities of embodied time inflect upon gender and subjectivity in Marieluise Fleißer's novel Mehlreisende Frieda Geier (1931). It analyzes how notions of "newness" and "modernity" are imbued in and divested from gendered subjects, the "Neue Frau" and the male athlete of Weimar modernity. Through a "mitbeteiligte" narration, Fleißer's narrator intimately masquerades the novel's characters and yet remains icily ironic. In striking this provocative balance, the text satirizes them and their attachment to the mythic individualist subject. The sociotemporal forces that mold subjects and endow them with social worth eclipse the characters' voluntarist beliefs during moments of violent masculine irredentism. Corroding personal pieties about gender, the subject, and time to reveal the "true" nature of modern existence, this paper argues for the novel's status as eminently modernist. This reading suggests alternative formulations of modernism through the ambivalent lens of the gendered subject.